Trial of the use of masks in the gynaecological operating theatre. - Chamberlain, G. V. (Royal College of Surgeons of England, 1984)
A randomly controlled trial was performed on 41 women having gynaecological surgery in which the team of surgeons and nurses wore or did not wear masks. After major abdominal surgery, 3 of 5 patients in the unmasked group developed wound infections whereas no infection was observed in the 4 patients of the masked group. A greater number of Streptococci were also found by settle-plates on the operating table in the unmasked group. No infection was recorded after minor or vaginal surgery.